Aerobic Exercise Only or in Combination with Resistance Exercise Provides a Significant Reduction in Blood Pressure: A Narrative Review - Winda Nurhamda; Arnengsih Nazir; Tertianto Prabowo (Jurnal Kardiologi Indonesia, 2026)
Hypertension is a major global health concern and a leading risk factor for cardiovascular disease. While pharmacological therapy remains central, lifestyle interventions, particularly Aerobic Exercise (AE), offer a cost-effective, safe, and sustainable strategy for reducing Blood Pressure (BP) and improving cardiovascular health. Evidence indicates AE consistently lowers Systolic Blood Pressure (SBP) more than Diastolic Blood Pressure (DBP), with clinically meaningful reductions in both. This review aimed to synthesize current evidence on the effects of AE, alone or combined with Resistance Training (RT) or dietary interventions, on BP in individuals with hypertension, elucidate underlying mechanisms, identify moderating factors, and evaluate safety considerations. A narrative review of English-language articles published from 2015 to 2025 was conducted via PubMed, including original and review studies, as well as selected textbooks. Keywords included “aerobic exercise”, “exercise”, “hypertension”, “blood pressure”, “coronary artery disease”, and “cardiovascular disease”. Eligible studies were synthesized into themes reflecting acute and chronic exercise responses, combination interventions, mechanistic pathways, influencing factors, and safety. Thirty-four publications (26 original articles, 6 reviews, 2 textbooks) were included. AE alone or combined with RT consistently reduced SBP, with smaller reductions in DBP, whereas the combination with a hypocaloric diet primarily enhanced cardiorespiratory fitness and body composition. Mechanisms include improved endothelial function, autonomic regulation, metabolic efficiency, and anti-inflammatory effects. Effect size was influenced by age, sex, Body Mass Index (BMI), medication use, exercise timing, and vascular stiffness. Safety data indicated high tolerability, minimal adverse events, and strong adherence. AE is a safe and effective non-pharmacological intervention for hypertension, producing clinically significant BP reductions, particularly in SBP. Combining AE with RT or dietary modification offers additional cardiometabolic benefits. These findings reinforce AE as a cornerstone of hypertension management and support its integration into routine clinical practice.